2015
DOI: 10.1111/jch.12745
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol Effects on Nitric Oxide Levels, Blood Pressure, and Renal Function in Kidney Transplant Patients

Abstract: In hypertensive kidney transplant recipients, the effects of nebivolol vs metoprolol on nitric oxide (NO) blood level, estimated glomerular filtration rate (eGFR), and blood pressure (BP) have not been previously reported. In a 12-month prospective, randomized, open-label, active-comparator trial, hypertensive kidney transplant recipients were treated with nebivolol (n=15) or metoprolol (n=15 CI,) compared with the metoprolol group younger than 50 years, the metoprolol group 50 years and older, and the nebivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“…First of all, the comparable BP‐lowering effect between nebivolol, previous BAAs and other antihypertensive agents was demonstrated in several studies including Stauffer et al, Santos et al and Duprez et al Nebivolol in antihypertensive combination therapy was likewise shown to have promising effects. The results of Grassi et al indicated that when using both office‐measured and holder BP monitoring, nebivolol is equal to AT 1 ‐R blockers regarding antihypertensive combination therapy with hydrochlorothiazide.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…First of all, the comparable BP‐lowering effect between nebivolol, previous BAAs and other antihypertensive agents was demonstrated in several studies including Stauffer et al, Santos et al and Duprez et al Nebivolol in antihypertensive combination therapy was likewise shown to have promising effects. The results of Grassi et al indicated that when using both office‐measured and holder BP monitoring, nebivolol is equal to AT 1 ‐R blockers regarding antihypertensive combination therapy with hydrochlorothiazide.…”
Section: Discussionmentioning
confidence: 91%
“…First of all, the comparable BP-lowering effect between nebivolol, previous BAAs and other antihypertensive agents was demonstrated in several studies including Stauffer et al, 80 Santos et al 81 85 that investigated the efficacy and tolerability of hypertensive treatment with byvalson and similarly found it to be very efficient. On this basis, nebivolol may be considered as first-line treatment in combination therapy.…”
Section: Discussionmentioning
confidence: 91%
“…Etkinlik çalışmalarında, nebivolol'ün kombinasyon tedavisi içerisinde de güçlü kan basıncı düşürücü etkiye sahip olduğu gözlenmiştir. [14][15][16] Bir araştırmada, hidroklorotiyazid ile kombine edildiğinde, nebivolol gerek klinik ölçümlerde gerekse ambulatuar ölçümlerde anjiyotensin reseptör blokerlerine (ARB) eşit ölçüde etkinlik göstermiştir. [17] Aynı şekilde nebivolol/valsartan kombinasyonu ile nebivolol'ün bu tür kombinasyonda da hayli etkin olduğu farkedilmiştir.…”
Section: Nebivolol Ve Antihipertansif Etkinlikunclassified